1990
DOI: 10.1111/j.1748-1716.1990.tb09021.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous nitric oxide as a probable modulator of pulmonary circulation and hypoxic pressor response in vivo

Abstract: The objective of this study was to investigate the role of endogenous nitric oxide, formed from L-arginine, in the regulation of pulmonary circulation in vivo, with special reference to the hypoxic pressor response. In artificially ventilated open-chest rabbits, pulmonary vascular resistance at normoxic ventilation (FIO2 = 21%) was 78 +/- 16 cmH2O ml-1 min 1000-1 (mRUL). Hypoxic ventilation (FIO2 = 10%) increased pulmonary vascular resistance to 117 +/- 17 mRUL. N omega-nitro-L-arginine methylester (L-NAME), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0
1

Year Published

1994
1994
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(109 citation statements)
references
References 25 publications
(11 reference statements)
4
103
0
1
Order By: Relevance
“…Cremona et al (1994) who used a similar preparation, also found that ¬_NAME did not alter pulmonary vascular resistance (PVR) during normoxia in dog lungs but raised it in the lungs of sheep, pigs and humans; in all four species, ¬_NAME raised pulmonary vascular resistance during hypoxic vasoconstriction (HPV). In rabbits, in vivo, Persson et al (1990) and, in intact cats Hyman et al McMahon et al (1991) found that NOS blockade raised Ppa during normoxia. However, in conscious dogs, Nishiwaki et al (1992) found no evidence that NO was released in the absence of experimental stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Cremona et al (1994) who used a similar preparation, also found that ¬_NAME did not alter pulmonary vascular resistance (PVR) during normoxia in dog lungs but raised it in the lungs of sheep, pigs and humans; in all four species, ¬_NAME raised pulmonary vascular resistance during hypoxic vasoconstriction (HPV). In rabbits, in vivo, Persson et al (1990) and, in intact cats Hyman et al McMahon et al (1991) found that NOS blockade raised Ppa during normoxia. However, in conscious dogs, Nishiwaki et al (1992) found no evidence that NO was released in the absence of experimental stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…A fall in cardiac output has also been observed in human subjects receiving NO synthase inhibitors (Petros et al, 1991) or the guanylate cyclase inhibitor, methylene blue (Schneider et al, 1992) as treatment for septic shock resulting in limitation of their use to treat this condition. The reason for the fall in cardiac output is unknown although increased afterload (Gardiner et al, 1990;Persson et al, 1990), reduced preload (Persson et al, 1990) direct myocardial action (Gardiner et al, 1990;Persson et al, 1990;Schulz et al, 1992), coronary vasoconstriction (Gardiner et al, 1990;Persson et al, 1990;Amrani et al, 1992;Schulz et al, 1992) and activation of baroreceptor reflexes (Kilbourn et al, 1990) have all been suggested. Inhibition of endocardial (Schulz et al, 1991) or myocardial (Schulz et al, 1992) NO synthesis are further potential mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, inhibition of NO synthesis induces vasoconstriction not only in the systemic, but also in the pulmonary (Persson et al, 1990;Perrella et al, 1991) and cor-onary (Amezcua et al, 1989) heart rate (HR, 1 min-') were monitored through a cannula containing 50 u heparin ml-' NaCl which was inserted into the right femoral artery. The cannula was connected to a pressure transducer (BRP-01, Experimetria, Budapest, Hungary) and a blood pressure coupler (HG-02, Experimetria).…”
Section: Introductionmentioning
confidence: 99%